2022
DOI: 10.1093/femsle/fnac043
|View full text |Cite
|
Sign up to set email alerts
|

The VirF21:VirF30 protein ratio is affected by temperature and impacts Shigella flexneri host cell invasion

Abstract: Shigella spp, the etiological agents of bacillary dysentery in humans, have evolved an intricate regulatory strategy to ensure fine-tuned expression of virulence genes in response to environmental stimuli. A key component in this regulation is VirF, an AraC-like transcription factor, which at the host temperature (37°C) triggers, directly or indirectly, the expression of >30 virulence genes important for invasion of the intestinal epithelium. Previous work identified two different forms of VirF with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The VirF protein is the master controller of the entire virulence system, and, given its pivotal role, many studies have been focused on its regulation, leading to the characterization of multiple mechanisms that contribute to its stringent regulation ( 15 , 17 21 ). VirF is a member of the AraC-XylS family of transcriptional activators, which are characterized by a 99- to 100-amino-acid segment containing two HTH motifs separated by an alpha helix ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The VirF protein is the master controller of the entire virulence system, and, given its pivotal role, many studies have been focused on its regulation, leading to the characterization of multiple mechanisms that contribute to its stringent regulation ( 15 , 17 21 ). VirF is a member of the AraC-XylS family of transcriptional activators, which are characterized by a 99- to 100-amino-acid segment containing two HTH motifs separated by an alpha helix ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The virF ORF can produce two forms of VirF: VirF 30 (30 kD) and VirF 21 (21 kD) by differential translation. 46 , 47 Therefore, we investigated whether fatty acids mediated the degradation of both these forms of VirF. We observed that VirF 30 was rapidly degraded by the exposure to c2-HDA ( Figure 5b ).…”
Section: Resultsmentioning
confidence: 98%
“…At temperatures similar to those of its host (37 °C), the binding of H-NS to the virF promoter is weakened, thereby allowing the production of the VirF protein [ 72 , 73 ]. A shorter version of VirF (VirF 21 ; MW 21 kDa), generated from an alternative translation initiation codon also contributes to repressing the production of the full-length VirF protein at 30 °C [ 74 , 75 ]. This regulatory mechanism may contribute to maintaining tight control of virulence, but its role in pathogenesis is unknown.…”
Section: The Major Virulence Gene Regulatory Cascade In Shi...mentioning
confidence: 99%